Acceptability and perceived side effects of insecticide indoor residual spraying under different resistance management strategies - Rodríguez Américo David; Penilla Rosa Patricia; Rodríguez Mario Henry; Hemingway Janet; Trejo Antonio; Hernández-Avila Juan Eugenio (Instituto Nacional de Salud Pública, 2006)
OBJECTIVE: To assess household acceptability and perceived side effects of residual indoor pyrethroid (PYR), carbamate and organophosphate insecticides sprayed by annual rotation (ROT), spatial mosaic (MOS), and a single insecticide (DDT or PYR) in communities of the coastal plain of Chiapas, Mexico. MATERIAL AND METHODS: A questionnaire to assess the acceptability and perceived side effects of indoor insecticides was administered to one member of 30% of the families in eight villages of Chiapas. The association of different insecticide treatments with their responses was evaluated (Chi-square). The intensity of side effects indicated under different treatments was compared in an ordered logistic model, using a severity index as the response variable. RESULTS: Insecticide spraying as a probable cause of symptoms was identified by 2.1% of interviewees. A significantly high percentage of persons with blurred vision, dizziness, sneezing, coughing, numbness, watery eyes, and itching lived in villages under MOS and ROT and a high severity index was significantly associated with ROT treatment. Reduction of mosquito bites and cockroaches were the perceived main benefits, and most villagers that perceived no benefits lived in DDT treated villages. Most of the interviewees welcomed spraying (83.7%), but the smell and having to remove furniture from houses were the main arguments against it. CONCLUSIONS: Acceptability correlated with insecticide spray coverage, although the most frequent suggestion for improvement was to increase the understanding of the objectives of spraying in the communities. The frequency of side effects was low, but higher in localities where a combination of insecticides was applied. This is a limitation for the use of this type of resistance management strategy in public health.